Influence of National Law on Jewish Law Using the Example of Jewish Marriage Law - Walter Homolka (Ancilla Iuris, 2022)
Jewish law has always co-existed with the surrounding legal cultures. Especially Samuel bar Abbas’s legal principle of “the law of the land is law” from the third century paved the way for an unproblematic adaptation of Jewish legal principles to square with the respective national law. When a Jewish state became re-established in 1948 parts of religious Jewish law became state-sanctionable, e.g. in matrimonial and inheritance law. This article tries to demonstrate the influence of national law on Jewish law using the example of Jewish marriage law.